2015
DOI: 10.1161/atvbaha.115.305729
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Aortic Regurgitation and Valvular Cardiomyopathy in Mice

Abstract: Objective We studied the mechanistic links between fibrocalcific changes in the aortic valve and aortic valve function in mice homozygous for a hypomorphic epidermal growth factor receptor mutation (Wave mice). We also studied myocardial responses to aortic valve dysfunction in Wave mice. Approach and Results At 1.5 months of age, prior to development of valve fibrosis and calcification, aortic regurgitation, but not aortic stenosis, was common in Wave mice. Aortic valve fibrosis, pro-fibrotic signaling, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Those mice, which are known as waved‐2 mice, however, are born with 3 discrete aortic valve cusps and rarely develop AS; the incidence of aortic valve dysfunction does not increase with age 13. Thus, to our knowledge, aortic valves in Velvet mice are unique among experimental models, in their resemblance to unicuspid valves in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those mice, which are known as waved‐2 mice, however, are born with 3 discrete aortic valve cusps and rarely develop AS; the incidence of aortic valve dysfunction does not increase with age 13. Thus, to our knowledge, aortic valves in Velvet mice are unique among experimental models, in their resemblance to unicuspid valves in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were stained with Alizarin Red or Picrosirius Red to quantitate the amount of calcium or collagen, respectively, as described previously 12. Movat's Pentachrome stain was used to visualize proteoglycans and collagen in the aortic valve, as described previously 13. Sources of primary antibodies for immunostaining were as follows: collagen‐1 (Abcam, Cambridge, MA), α‐smooth muscle actin (α‐SMA; Abcam), Runx2 (Santa Cruz Biotechnology, Dallas, TX), and CD31 (BD Biosciences, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This was paralleled by left ventricular hypertrophy, increased LV end diastolic dimension, and total stroke volume. Valve proteoglycan content was increased at this young age, but not calcification, demonstrating that myxomatous semilunar valves are present before the development of calcific disease.…”
Section: See Accompanying Article On Page 1653mentioning
confidence: 93%
“…1, 2 Hajj et al revisit a previously reported mouse homozygous for a single nucleotide mutation in the gene encoding the epidermal growth factor receptor (EGFR), resulting in a 90% global reduction in EGFR-tyrosine kinase activity. 3 Egfr Wa2/Wa2 , or waved-2 (Wave) mice, had been previously reported to develop abnormalities of the semilunar valves.…”
mentioning
confidence: 99%